Modification of polymethylmethacrylate under irradiation of the SEM electron beam. Issue 11 (2nd December 2022) - Havranek, Vladimir; Torrisi, Lorenzo; Silipigni, Letteria; Mackova, Anna; Malinsky, Petr; Cutroneo, Mariapompea
Abstract : This paper is focused on the study of the modifications of polymethymethacrylate (PMMA) under the irradiation of electron beams. PMMA is a well-known thermoplastic synthetic polymer, with unique features such as transparency, good tensile strength, and moldability. Its performance can be significantly modified through the realization of functionalized thin film coatings, ion irradiations, laser irradiations for different applications, such as flexible electronics, biomaterials, dielectric layers and sensors. The purpose of this paper is to describe the changes of the PMMA features as a function of the energy and fluence of electron beams. The morphology of the obtained structures is studied by electron scanning microscopy while the C/ O atomic ratios are monitored by the energy dispersive X-ray spectroscopy.